2018
DOI: 10.1016/j.stemcr.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A Humanized Mouse Model Generated Using Surplus Neonatal Tissue

Abstract: SummaryHere, we describe the NeoThy humanized mouse model created using non-fetal human tissue sources, cryopreserved neonatal thymus and umbilical cord blood hematopoietic stem cells (HSCs). Conventional humanized mouse models are made by engrafting human fetal thymus and HSCs into immunocompromised mice. These mice harbor functional human T cells that have matured in the presence of human self-peptides and human leukocyte antigen molecules. Neonatal thymus tissue is more abundant and developmentally mature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…The limited availability of said human fetal tissues creates logistical and operational constraints. Recently, a novel BLT-like humanized mouse model has been developed using non-autologous human cord blood-derived HSCs and human neonatal/pediatric thymus, which enable investigators to construct > 1000 BLT-like humanized mice using cryopreserved thymus tissues and readily available cord blood-derived HSCs [96]. Recent studies demonstrate that these BLT-like humanized mice develop human immune cells, support HIV infection and replication, and exhibit anti-HIV immune response (unpublished data from Elie Haddad, Chloé Colas, et al, at the CanCure 5th Annual General Meeting-2019, Poster Session, in Montreal, Canada).…”
Section: Bone Marrow-liver-thymus (Blt)-humanized Mouse Modelmentioning
confidence: 99%
“…The limited availability of said human fetal tissues creates logistical and operational constraints. Recently, a novel BLT-like humanized mouse model has been developed using non-autologous human cord blood-derived HSCs and human neonatal/pediatric thymus, which enable investigators to construct > 1000 BLT-like humanized mice using cryopreserved thymus tissues and readily available cord blood-derived HSCs [96]. Recent studies demonstrate that these BLT-like humanized mice develop human immune cells, support HIV infection and replication, and exhibit anti-HIV immune response (unpublished data from Elie Haddad, Chloé Colas, et al, at the CanCure 5th Annual General Meeting-2019, Poster Session, in Montreal, Canada).…”
Section: Bone Marrow-liver-thymus (Blt)-humanized Mouse Modelmentioning
confidence: 99%
“…We, and others, have begun to utilize humanized mouse models to study immunotherapy with PDXs [44,46,47]. At our institution, the Brown and Burlingham groups have developed a NeoThy humanized mouse model using non-fetal human tissue (i.e., cryopreserved neonatal thymus and umbilical cord blood HSC) that harbors functional human hematopoietic cells [49]. We have used NeoThy mice to successfully engraft multiple human PDXs and have demonstrated that they harbor functional immune cells (currently unpublished data).…”
Section: Humanized Modelsmentioning
confidence: 99%
“…However, a major limitation of the BLT model is its absolute reliance on fetal tissues. Therefore, alternative approaches involving the engraftment of immunodeficient mouse strains with embryonic stem cell-derived, thymic epithelial progenitors [293], or with neonatal thymus [294], have been recently proposed.…”
Section: Human Microenvironment and Lymphocyte Educationmentioning
confidence: 99%